KAJIAN SISTEM PENGEMASAN BUNGA MAWAR POTONG (Rosa hybrida) SELAMA PENYIMPANAN UNTUK MEMPERPANJANG MASA PAJANGAN - Rokhani Hasbullah; Suroso .; Desy Nofriati (PERTETA, 2006)
ABSTRACT Pretreatment and packaging or rose cut flowers during stroage and transportation should be designed in order to keep its quality during vase life of the flowers. The objective of this study was to find out the pulsing solution and the design of packaging to prolong the vase life of the rose cut flowers. The flowers were harvested from Loji, Cipanas, when the flower was at two bud open stages. Before storage, the flowers were pulsed in the chemical solution of sucrose, glyserin, Na-benzoat and citric acid at different concentrations. Each 20 cuts of flower were placed in the boxes of 60 ´ 15 ´ 7 cm3with different ventilation system. The result showed that the pulsing solution with 3 % sucrose, 25% glyserin, 300 ppm Na-benzoat and 375 ppm citrit acid caused a signioficant decrease in the respiration rate and prolonged the vase life of the flowers. The packaging model gave an effect of modified atmospheric environment inside the packaging and significantly affected the flower quality during stronge. The result suggested that the use of the packaging with the ventilation of 3.5 cm in diameter using polypropilene film would be suitable for rose cut flowers packaging during storage. The packaging model prolonged the vase lilfe of the flowers until 6 days after 5 days of storage and decreased the flowers senescene up to 20-25%. Keyword: rose cut flower, pulsing solution, modified atmosphere packaging, vase life.